2016
DOI: 10.1093/hmg/ddw359
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated pupillary light responses and downregulation of opsin expression parallel decline in circadian disruption in two different mouse models of Huntington’s disease

Abstract: Circadian deficits in Huntington’s disease (HD) are recapitulated in both fragment (R6/2) and full-length (Q175) mouse models of HD. Circadian rhythms are regulated by the suprachiasmatic nuclei (SCN) in the hypothalamus, which are primarily entrained by light detected by the retina. The SCN receives input from intrinsically photosensitive retinal ganglion cells (ipRGCs) that express the photopigment melanopsin, but also receive input from rods and cones. In turn, ipRGCs mediate a range of non-image forming re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…For double-labeling experiments, both primary and secondary antibodies were incubated simultaneously. Because both CRY1 and melanopsin antibodies are raised in rabbit, colocalization of CRY1 within ipRGCs was performed using anti-CRY1 and anti–green fluorescent protein antibodies on retinal sections from OPN4.Cre.eYFP mice obtained from previous studies (25). …”
Section: Methodsmentioning
confidence: 99%
“…For double-labeling experiments, both primary and secondary antibodies were incubated simultaneously. Because both CRY1 and melanopsin antibodies are raised in rabbit, colocalization of CRY1 within ipRGCs was performed using anti-CRY1 and anti–green fluorescent protein antibodies on retinal sections from OPN4.Cre.eYFP mice obtained from previous studies (25). …”
Section: Methodsmentioning
confidence: 99%
“…The SCN synchronizes to the LD of the environment through the action of light received by the light-sensitive retinal ganglion cells (Panda et al, 2002;Ruby et al, 2002). Both R6/2 and Q175 mice-a HD model with slower phenotype development-exhibit progressive retinal morphologic changes, including a downregulation in the expression of melanopsin and cone opsin, markers of retinal light-sensitive and cone cells, respectively (Ouk et al, 2016b;Lin et al, 2019). Photodetection appeared to be progressively impaired in R6/2 mice because they exhibited attenuation in their PLR from 12 weeks of age for light at low intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The first component of the circadian system to be disrupted in HD may be the retinal dysfunction and degeneration that has been described in R6/2 and other HD mice models (Helmlinger et al, 2002;Petrasch-Parwez et al, 2004;Batcha et al, 2012;Ragauskas et al, 2014). A recent study has found deficits in retina function of the R6/2 mouse that might cause disruption of light transmission to the SCN (Ouk et al, 2016b). That study reported a decrease in pupillary light responses (PLRs; or the ability of the pupil to constrict in response to light, a marker of light reception in the retina) that is correlated with down-regulation of the photopigments melanopsin and cone opsin in both R6/2 mice and a full-length knock-in mouse model of HD (Ouk et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…121 Degeneration of cone and melanopsin pathways has also been reported in a mouse model of Huntington's disease. 122 All these data suggest alteration of both retinal photoreception and photic signal transmission necessary to entrain the retinal and the central clocks in several degenerative diseases. Using impaired circadian photoreception as a marker or biological indicator of retinal or brain pathologies will represent a valuable research tool for diagnostic purposes.…”
mentioning
confidence: 99%